Uncovering the influence of demographic factors on the emotional regulation of Alpha generation students in Islamic educational institutions in Indonesia: the role of parenting style as a mediator - Hidayat Ma’ruf; Ahmad Juhaidi; Muhammad Rafiq Hafiz; Salafuddin Fitri (Cogent Education)
Parents face increasing challenges in educating Generation Alpha, yet limited research addresses this issue in Indonesia’s Islamic school context. This study investigates the direct effects of parental demographic background—namely, child’s gender, number of children, parental age, and education—on students’ emotional regulation, and examines the mediating role of parenting style. Data from 201 parents of elementary and junior Islamic school students were analyzed using PLS-SEM. Results show that permissive parenting had a strong positive effect on emotion regulation, while authoritarian and authoritative styles had limited or negative impacts. Child gender was weakly and negatively associated with authoritative parenting. The number of children correlated negatively with emotional regulation but showed low influence on permissive parenting, similar to parental age. Parental education showed strong negative associations with both authoritarian and permissive styles and had the strongest negative effect on authoritarian parenting. In Islamic education contexts, higher-educated parents were less likely to adopt authoritarian styles. The mediating roles of permissive and authoritarian parenting between parental education and emotion regulation were minimal. These findings underscore the importance of culturally contextualized parenting strategies in Islamic schools and call for further research on their long-term and cross-cultural applicability.